Investigating the macular choriocapillaris in early primary open-angle glaucoma using swept-source optical coherence tomography angiography - Lun, Katherine; Sim, Yin Ci; Chong, Rachel; Wong, Damon; Tan, Bingyao; Husain, Rahat; Aung, Tin; Sng, Chelvin C. A.; Schmetterer, Leopold; Chua, Jacqueline (Frontiers in Medicine, 2022)
Introduction There has been a growing interest in the role of vascular factors in glaucoma. Studies have looked at the characteristics of macular choriocapillaris in patients with glaucoma but with conflicting results. Our study aims to use swept-source optical coherence tomography angiography (SS-OCTA) to evaluate macular choriocapillaris metrics in normal participants and compare them with patients with early primary open-angle glaucoma (POAG) (mean deviation better than −6dB). Methods In this prospective, observational, cross-sectional study, 104 normal controls (157 eyes) and 100 patients with POAG (144 eyes) underwent 3 mm × 3mm imaging of the macula using the Plex Elite 9000 (Zeiss Meditec, Dublin, CA, USA). Choriocapillaris OCTA images were extracted from the device’s built-in review software and were subsequently evaluated for the density and size of choriocapillaris flow deficits. Results After adjusting for confounding factors, the density of flow deficits was independently higher in those aged 53 years and above (P ≤ 0.024) whereas the average flow deficit size was significantly larger in those aged 69 years and above (95% CI = 12.39 to 72.91; P = 0.006) in both normal and POAG patients. There were no significant differences in the density of flow deficits (P = 0.453) and average flow deficit size (P = 0.637) between normal and POAG participants. Conclusion Our study found that macular choriocapillaris microvasculature on SS-OCTA is unaltered by subjects with POAG. This suggests that OCTA macular choriocapillaris may not be potentially helpful in differentiating early glaucoma from healthy eyes.